BRAND PERSONALITY TOWARD CUSTOMER PURCHASE INTENTION: THE INTERMEDIATE ROLE OF ELECTRONIC WORD-OF-MOUTH AND BRAND EQUITY - Hojjat Vahdati,; Seyed Hadi Mousavi Nejad, (Asian Academy of Management Journal, 2016)
Organizations like banks with the ability to develop an understanding of and capability in predicting customer's behaviour are organisations that have an edge over their competitors in the marketplace. One way of how organization's competitive advantage can be achieved is when they can determine their customer's purchase intention of products. This study attempts to investigate if brand personality, e-WOM and brand equity are determining factors that influence bank's customers purchase intention which can lead to their purchase decision later. Here, Mellat Bank in Iran is used as a case study and the bank's customers participated as respondents in a survey. The study tested seven hypotheses using structural equation modeling techniques. The findings show that brand personality, e-WOM and brand equity have positive and significant effects on customer's purchase intentions. The results also reveal that these factors have positive internal effects on each other. In addition, e-WOM and brand equity show positive mediator roles.